Content Development: Character-Based Technopreneurship Education for Young Ganesha Entrepreneurs - Kertiasih, Ni Ketut; Setemen, Komang; Permana, Agus Aan Jiwa (Asian Journal of Science, Technology, Engineering, and Art, 2024)
These reforms should focus on curriculum updates, graduate competencies, teacher qualifications, funding, and the decentralization of education. One of the key responsibilities of educators is to innovate teaching materials, ensuring they prepare graduates with the necessary technological skills for future careers or entrepreneurship. The introduction of the "Technopreneurship" course under the "Merdeka Curriculum" has been positively received by students, as it equips them with practical skills such as business idea generation, market analysis, and financial proposal creation. However, many students face challenges in maintaining program continuity after receiving funding, with some misusing the funds for personal purchases. This situation underscores the moral obligation of instructors to guide students in becoming ethical entrepreneurs. To address these issues, it is essential to develop case studies that integrate character education into technopreneurship, promoting not only business skills but also honesty, responsibility, and a commitment to social values.